THE IMPACT OF ANTITUBERCULOSIS DRUG-INDUCED HEPATOTOXICITY TO SUCCESFUL TUBERCULOSIS TREATMENT IN INDONESIA - Maria, Nisa; Radji, Maksum; Burhan, Erlina (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study aimed to evaluate the impact of antituberculosis (anti-TB) drug-induced hepatotoxicity (DIH) to outcome TB treatment. Methods: A cohort retrospective study conducted at a tertiary hospital in Jakarta - Indonesia, from the period of 2013-2016. A total of 76 samples of TB patient with and without anti-TB DIH were analyzed. Results: Successful outcome TB treatment for TB patient with anti-TB DIH is 47.4% compared to TB patient without anti-TB DIH is 78.9%. Relative risk (RR) analysis showed that risk of unsuccessful TB treatment for TB patient with anti-TB DIH is 2.50 fold higher (95% confidence interval: 1.259- 4.960) than TB patient without anti-TB DIH. Age, sex, and comorbidities are not statistically significant to outcome TB treatment. For TB patient with anti-TB DIH, onset anti-TB DIH and recurrence anti-TB DIH also not statistically significantly influence outcome TB. The mean duration of treatment for a successful outcome for TB patient with and without anti-TB DIH was statistically significant (p<0.05), respectively, 8.44Â±1.85 and 6.52Â±0.93 months. Conclusion: Anti-TB DIH increases the risk of unsuccessful and prolonged duration TB treatment.